# If x = 1 is a zero of the polynomial f (x) = x3 – 2x2 + 4x + k, write the value of k.

Given,

f(x) = x3 – 2x2 + 4x + k

x = 1 is a zero,

So,

Keeping x = 1 we get,

f(1) = 13 – 2(1)2 + 4×1 + k

f(1) = 1 – 2 + 4 + k

f(1) = 5 – 2 + k

f(1) = 3 + k

– 3 = k

So we get,

k = – 3

Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Related Videos
Champ Quiz |Revealing the relation Between Zero and Coefficients38 mins
Relation Between zeroes and Coefficients46 mins
Interactive Quiz - Geometrical Meaning of the Zeroes32 mins
Relationship between Zeroes and Coefficients-238 mins
Relationship between Zeroes and Coefficients-152 mins
Quiz - Division Algorithm38 mins
Interactive Quiz:Polynomials43 mins
Division Algorithm-130 mins
Relation b/w The Zeroes and Coefficients of Cubic Polynomials54 mins
Revision of Relation Between the Zeroes and Coefficients of Quadratic Polynomial46 mins
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
view all courses